A Study on the Status, Citation Analysis, and Altmetric Indices of Journals of Golestan University of Medical Sciences - Masoud Mohammadi; Masoumeh Mirkarimi; Zohereh Paranam; Maryam Banisafar; Rezanezhad Marzieh Rezanezhad; Mahin Tatari; Mohammad Mahboubi (Golestan University of Medical Sciences, 2020)
Background: Journals are regarded as the most important media for transferring knowledge and research results, accordingly their promotion is conditioned by continuous evaluation and improvement of performance. The present study aimed to determine the status, citation analysis, and altmetric indices of journals published by Golestan University of Medical Sciences. Methods: This cross-sectional study was conducted by a descriptive approach with scientometric and citation analysis methods in 2019. The statistical population consisted of 5 journals of Golestan University of Medical Sciences. Data collection tool was a researcher-made checklist consisting of 28. Altmetric indices of journals were also evaluated. Data was analyzed by descriptive statistics; and the results were presented in diagrams and tables. Results: All the studied journals had all "publication requirements. Only one journal had the requirement, "at least half of editorial board should be outside of the publication". Moreover, 37 percent of 105 editorial board members in the under examined journals had extra-organizational affiliation and only 8 percent were from abroad. The articles of "Journal of Gorgan University of Medical Sciences " was the most-cited article regarding citation bases. Conclusions: Journals of Golestan University of Medical Sciences need to revise their structures, especially for editorial board members namely being international, having an organizational affiliation outside the university, as well as the presence of editorial board members with further research activity and background.